1997
DOI: 10.2307/4089248
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Wood Duck Eggs in Relation to Egg Size, Laying Sequence, and Skipped Days of Laying

Abstract: We collected 138 freshly laid Wood Duck (Aix sponsa) eggs from 13 nests to determine the effects of egg size, laying sequence, and skipped laying days on egg composition. All components except yolk ash and eggshell, both wet and dry, increased in direct proportion to fresh-egg mass. Egg size increased during the first half of laying and decreased thereafter. The effects of laying sequence were component-specific. Absolute levels of neutral lipids (comprising 65.6% of dry yolk) were near average until about 75%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 42 publications
(13 reference statements)
1
35
3
Order By: Relevance
“…If the maternal condition of gulls was manipulated by supplementary feeding, extra protein diets increase yolk content of the c-egg (Bolton et al 1992). Maternal effects that operate via the eggs may be important and, for instance, larger eggs provide greater lipid and water resources (Williams 1994;Kennamer et al 1997). Nevertheless, in our experiment egg size and the interaction between egg size and sex did not affect embryo survival.…”
Section: Discussionmentioning
confidence: 60%
“…If the maternal condition of gulls was manipulated by supplementary feeding, extra protein diets increase yolk content of the c-egg (Bolton et al 1992). Maternal effects that operate via the eggs may be important and, for instance, larger eggs provide greater lipid and water resources (Williams 1994;Kennamer et al 1997). Nevertheless, in our experiment egg size and the interaction between egg size and sex did not affect embryo survival.…”
Section: Discussionmentioning
confidence: 60%
“…We also considered the possibility that eggs laid by an individual Wood Duck may vary in size more than those laid by an individual Common Goldeneye. The Wood Duck lays smaller eggs at the beginning and end of the laying cycle, with larger eggs in the middle, so variation within a female can be quite substantial (Kennamer et al 1997). Hepp et al (1987) and Kennamer et al (1997) reported considerable variation among eggs (CV 8.0%, 4.0%, 2.7% and 6.4%, 3.5%, 2.4% for mass, length, and breadth, for each respective study).…”
Section: Discussionmentioning
confidence: 92%
“…The Wood Duck lays smaller eggs at the beginning and end of the laying cycle, with larger eggs in the middle, so variation within a female can be quite substantial (Kennamer et al 1997). Hepp et al (1987) and Kennamer et al (1997) reported considerable variation among eggs (CV 8.0%, 4.0%, 2.7% and 6.4%, 3.5%, 2.4% for mass, length, and breadth, for each respective study). The Bufflehead (Bucephala albeola) and Barrow's Goldeneye (B. islandica) vary comparably in these same egg measurements with CVs of 5.89%, 3.33%, 2.13% and 5.04%, 3.06%, 2.10%, respectively (Lavers et al 2006).…”
Section: Discussionmentioning
confidence: 92%
“…Thus, it seems that altricial species change egg size by increasing the amount of albumen while keeping yolk content relatively constant, whereas precocial species tend to alter egg size by increasing both yolk and albumen content with an increase in egg mass. Further support for this pattern has been observed in precocial wood ducks Aix sponsa (Kennamer et al, 1997) and ruddy ducks Oxyura jamaicensis (Pelayo and Clark, 2002), which lay eggs having yolk and albumen varying isometrically with egg mass, and in altricial great tit Parus major eggs, in which much of the variation in egg mass is attributable to variation in albumen mass (Lessells et al, 2002).…”
Section: Scaling Of Egg Compositionmentioning
confidence: 93%